Two Face Personality in Identity Falsification and Catfishing Behavior on Online Dating Tinder - Amelya Kristy; Nanang Krisdinanto; Akhsaniyah Akhsaniyah (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2023)
This research stems from using online dating, originally used to make it easier for users to find friends, relationships, or partners. However, online dating is often used to practice catfishing or identity fraud. This phenomenon arises as an implication of the ease of creating more than one personal account, which is used as a reflection of the identity that the perpetrator wants to display. This topic is related to the theme of computer-mediated communication (CMC), which allows individuals to communicate asynchronously, which makes it easier for perpetrators to find victims. This research aims to find out the experiences of catfishing perpetrators and how they interpret the experience of doing so. This research uses the phenomenological method, where each informant constructs meaning through their intersubjective side. Data collection techniques were conducted through in-depth interviews to obtain results from a first-person perspective. The results of this research describe the experience of catfishing perpetrators interacting and finding victims in online dating applications. In addition, the research also found that the perpetrators interpreted their catfishing practice not only as the fulfillment of sexual desires but also as the fulfillment of desires that are not in the real world (wanting to be praised, recognized, and have a sense of pride). The experiences and meanings of the research subjects reflect modernity and the fulfillment of sexual desires online. Unlike several previous studies, this phenomenological research can see the depth of the essence of catfishing behavior because it uses original data extracted from the perpetrator’s experience (first party).